Decision-Making Analysis for Sustainable Tourism Development: A DEMATEL and SEM Approach to Infrastructure and Policy Optimization in Ethnic Village Tourism - Tao, Xiaoning; Nor Akmar, Abdul Aziz; Syamsul Herman, Mohammad Afandi; Suziana, Hassan (Decision Making: Applications in Management and Engineering, 2025)
Achieving sustainable tourism development necessitates the utilisation of structured decision-making frameworks that effectively reconcile economic advancement, cultural heritage conservation, and infrastructural limitations. This research adopts the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach in conjunction with structural equation modelling (SEM) to pinpoint and assess the principal determinants influencing sustainable tourism within the context of strategic planning for ethnic village tourism. Focusing on the Xijiang Miao Village in China, the study incorporates semi-structured interviews and expert assessments to evaluate variables such as economic investment, infrastructure limitations, governance and managerial practices, cultural preservation efforts, and ecological sustainability. The analysis underscores the significance of multiple sub-elements associated with these core dimensions. Furthermore, through the application of SEM, the findings reveal that governance and policy (β = 0.222), alongside economic and resource management (β = 0.176), exert a favourable influence on sustainable development via enhanced strategic decision-making processes. Conversely, environmental and risk management (β = -0.804), infrastructure planning (β = -0.085), and the extent of stakeholder engagement in decision-making (β = -0.074) demonstrate adverse effects. This study enriches both qualitative and quantitative decision-support models by showcasing the integration of DEMATEL and SEM methodologies to refine strategic planning mechanisms in the realm of sustainable tourism. The insights derived are expected to guide key stakeholders, including governmental bodies, tourism authorities, and infrastructure developers, in formulating more effective policies and initiatives.